DECONSTRUCTING THE CHRISTIAN NARRATIVE IN THE PHILIPPINES: Decolonizing Religious Studies and Recognizing Marginalized Communities - Kadir, Mohd Amin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The Philippines is often portrayed as the only “Catholic nation” in Asia—a narrative deeply rooted in the legacy of Spanish colonialism and perpetuated by religious institutions and the national education system. However, this singular identity conceals the rich diversity of spiritual traditions present across the archipelago, including Muslim Moro communities, Lumad indigenous groups, and practitioners of local ancestral belief systems. This article interrogates the intersection of religion, colonialism, and knowledge-power through a decolonial and collective-reflective approach. Employing a critical narrative methodology, the study draws on the lived experiences of five individuals from diverse religious and ethnic backgrounds. Their reflections are analyzed through the theoretical lenses of decoloniality, subaltern epistemologies, and critical sociology of religion. The findings reveal that religious studies in the Philippines continue to be shaped by hegemonic Catholic narratives, which marginalize non-dominant spiritualities through persistent epistemic violence. Nevertheless, the narratives also illuminate how local spiritualities function as sites of resistance and survival against these colonial legacies. This article contributes to the growing movement to decolonize religious studies in Southeast Asia by asserting the centrality of epistemic and spiritual plurality. Decolonization, as argued here, is not merely about inclusion, but about dismantling the very structures of knowledge that have historically silenced alternative voices—and rebuilding a more equitable, dialogical, and just academic field.